(untitled) (Progressive Agriculture, 2014)
South Asian countries have made remarkable advances in food production accompanied by a dramatic reduction of poverty during the past two decades. This has been due to the result of trade and investment reforms, which have generated economic growth in this region. Despite these changes South Asia generates only 2% of the global income, yet supports 22% of the worlds population and 44% of the worlds poor. Over 75% of the population depends directly or indirectly on agriculture for their livelihoods. Therefore, agriculture will play a major role in the future and massive productivity increases and product diversification will be required. Due to escalating population and urbanization, natural resources are gradually depleting posing major challenges to reduce poverty in this region. The problems confronting these countries are complex and enormous of which the major issues are; declining agricultural land and agricultural population, marginal producers with small land holdings, decreasing per capita land availability, conflicting demands for scarce water resource, urbanization and youth evading traditional farming. This region will be required to produce food for larger and larger populations from less and lees land. The biggest challenge is how to increase output from the shrinking agricultural sector, while sustaining the productivity potential of the available natural resources. The agricultural production systems are changing rapidly in these countries, trend being intensive agriculture using high- tech that provides maximum potential benefit of improved crop germplasm. Agriculture is the largest contributor to the economies of many countries of the developing world. Agricultural biotechnology, which comprises a wide range of biological disciplines, offers enormous potential to speed up the development of plant varieties with pro-poor traits such as drought tolerance, pest resistance or tolerance, higher yields, increased nutritional value, among others. While biotechnology does not provide the silver bullet for poverty alleviation, it does enhance the effectiveness of other disciplines such as plant breeding, integrated pest and nutrient management, and livestock breeding, feeding and disease management.